KINERJA BIDANG LALULINTAS ANGKUTAN JALAN DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMASI KABUPATEN BANJAR - Ade Hermawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The goal in this research were: 1) to know the performance of Road Freight Traffic Field Office of transportation, communication and Informatics of Banjar Regency. 2) to find out the factors that affect the performance of Road Freight Traffic Field Office of transportation, communication and Informatics of Banjar Regency.This research uses the method of evaluation. The population was the user community Traffic Road Transport Department of transport, communications and Informatics Banjar Regency. The technique of sampling was done using a sampling aksidental. Data collection techniques used are documentation and interviews. Data analysis techniques was done qualitatively.The results showed: 1) Road Transit Traffic Field Performance of Department of transport, communications and Informatics Banjar Regency is at a good level. 2) factors that affect the performance of Road Freight Traffic Field Performance of Department of transport, communications and Informatics Banjar Regency is the purpose, organizational structures, and human resources.